2014
DOI: 10.1111/trf.12905
|View full text |Cite
|
Sign up to set email alerts
|

p38MAPK is involved in apoptosis development in apheresis platelet concentrates after riboflavin and ultraviolet light treatment

Abstract: These findings revealed that p38MAPK is involved in signaling leading to apoptosis triggered by RF-PI. Elucidation of the biochemical processes influenced by PI is a necessary step in the development of strategies to improve the PLT quality and ameliorate the negative effects of PI treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
48
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 30 publications
(51 citation statements)
references
References 49 publications
3
48
0
Order By: Relevance
“…15,25 In this study, we further show that this compound inhibits the mitochondrial translocation of Bax and Bid in RF/UVtreated PLTs and protects mitochondrial integrity by decreasing cyto c release and loss of DW m , effects that might explain the reduced PS exposure and caspase activities we previously reported when this inhibitor was used. 25 Although intensive investigations have reported that p38 signaling plays a critical role in modulating cell activities by either promoting apoptosis or enhancing cell survival, 22 its function in PLT apoptosis remains unclear.Rukoyatkina and coworkers 35 showed that p38 is involved in PLT apoptosis using a BH3 mimic compound ABT-737. p38 signaling is also involved in PLT apoptosis triggered by staurosporine, a microbial alkaloid, showing that inhibition of p38 decreases the loss of DW m and PS exposure.…”
supporting
confidence: 73%
See 4 more Smart Citations
“…15,25 In this study, we further show that this compound inhibits the mitochondrial translocation of Bax and Bid in RF/UVtreated PLTs and protects mitochondrial integrity by decreasing cyto c release and loss of DW m , effects that might explain the reduced PS exposure and caspase activities we previously reported when this inhibitor was used. 25 Although intensive investigations have reported that p38 signaling plays a critical role in modulating cell activities by either promoting apoptosis or enhancing cell survival, 22 its function in PLT apoptosis remains unclear.Rukoyatkina and coworkers 35 showed that p38 is involved in PLT apoptosis using a BH3 mimic compound ABT-737. p38 signaling is also involved in PLT apoptosis triggered by staurosporine, a microbial alkaloid, showing that inhibition of p38 decreases the loss of DW m and PS exposure.…”
supporting
confidence: 73%
“…1 Previously, we and others have demonstrated that inhibition of the stress kinase p38 improves PLT in vitro quality with or without RF/UV treatment during storage, showing a deceleration of apoptosis development. 15,25,29 Here we provide further insights into the mechanism of the impact of RF/UV treatment on PLT mitochondrial function and demonstrate that some of these activities are also modulated by p38 MAPK. Accumulating evidence demonstrates that PI-treated PLTs share highly similar behaviors with PLTs stimulated by physiologic activators, including PLT activation, degranulation, and development of apoptosis, leading to the conclusion that these processes have the same signaling mechanism.…”
Section: Discussionmentioning
confidence: 60%
See 3 more Smart Citations